2005
DOI: 10.1002/jgm.730
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine production by dendritic cells genetically engineered to express IL‐4: induction of Th2 responses and differential regulation of IL‐12 and IL‐23 synthesis

Abstract: Japan Arthritis Res Ther 2003, 5(Suppl 3):1 (DOI 10.1186/ar800) Apoptosis is a principal mechanism in metazoans by which superfluous or potentially harmful cells are eliminated. Deregulation of this process leads to a variety of diseases such as cancer and autoimmune diseases. Stimuli that can induce apoptosis are relatively diverse, and include the death factors (Fas ligand, tumor necrosis factor and TRAIL), DNA damage, and oxidative stress. Regardless of the origin of the apoptotic stimulus, commitment to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…Neutralizing IFN␥ has been shown to increase the generation of Th17 cells (28,29). IL-4 DCs produce increased amounts of IL-12 and IFN␥ after stimulation with lipopolysaccharide or CD40L (25). We also evaluated the effect of IL-12 and IFN␥ in our system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neutralizing IFN␥ has been shown to increase the generation of Th17 cells (28,29). IL-4 DCs produce increased amounts of IL-12 and IFN␥ after stimulation with lipopolysaccharide or CD40L (25). We also evaluated the effect of IL-12 and IFN␥ in our system.…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 is a potent inducer of IFN␥ (19,30), and it has recently been shown that inhibition of IFN␥ can enhance the development of IL-17-producing T cells (28). IL-4 DCs produce increased quantities of IL-12 and IFN␥, as compared with untransduced DCs, after stimulation with CD40L and lipopolysaccharide (25) (Figure 1A). We therefore evaluated the role of IL-12 and IFN␥ in our system.…”
Section: Role Of Il-12 and Ifn␥ In Il-4 Dc-mediated Suppression Of Ilmentioning
confidence: 96%
See 2 more Smart Citations
“…The threshold cycle is the PCR cycle at which an increase in the fluorescent emission above the baseline signal is first detected. Since the values of the threshold cycle decrease proportionally with increased target quantity, they were used to determine the relative cDNA amounts in each sample and to evaluate levels of p22phox, p47phox, gp91phox, and eNOS messenger RNA 1828 HARUNA ET AL (mRNA), which were normalized to the quantity of GAPDH mRNA as described previously (24). Measurement of fluvastatin, adiponectin, and BH 4 .…”
Section: Rna Isolation and Real-time Quantitative Reverse Transcriptamentioning
confidence: 99%